(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Urban green tourism space accessibility is one of the important indicators for measuring urban livability, and has significant implications for social equity and people’s wellbeing. This article takes Zhengzhou city as the research object, and uses land use data, commercial housing transaction data, population density data, Gaussian two-step moving search method, and GWR geographic weighted regression model method to analyze and calculate the temporal and spatial matching between urban green tourism space accessibility and residents’ behavior preferences. The main findings are as follows: (1) overall, green spaces within the core area of Zhengzhou city show lower values in the central region but higher values in the eastern and western regions, indicating large spatial differences. (2) The distribution of residents’ demand for green tourism space accessibility shows significant differences in the central and eastern regions. (3) The spatial matching degree between green tourism space accessibility and residents’ behavior preferences within the Fourth Ring Road of Zhengzhou city is generally high, with high matching degrees in the central and eastern areas and low matching degrees in the northern and southern areas, reflecting the unfairness in the distribution of green tourism space. The article puts forward planning and construction suggestions and viewpoints to address the existing unfairness problems and phenomena.